Penerapan model pembelajaran Snowball Throwing untuk meningkatkan hasil belajaran pada siswa kelas II SDN 01 Kalirejo Talun - Siti Nurasiyah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The scope of elementary Indonesian subjects includes language and literary skills, namely listening, speaking, reading and writing (Khasanah, 2015). For this reason, the purpose of this research is the application of thelearning model snowball throwing to improve learning outcomes for second grade students at SDN 01 Kalirejo Talun. This type of research is Classroom Action Research (CAR). The subjects in this study were 19th graders of SDN 01 Kalirejo Talun. Data collection methods used in this study are tests, observations, documentation and interviews. The data analysis technique used is descriptive both qualitatively and quantitatively. For the success criteria in this study, the indicator of success in this study is individual learning completeness if the proportion of students' correct answers is more than the predetermined KKM and for classical learning completeness if at least 85% of students score above the predetermined KKM, which is 75. The results of In this study, cycle 1 shows that the number of students who have reached the predetermined KKM is 14 students with a percentage of 78.95%. Meanwhile, the results of cycle 2 show that the number of students who have reached the predetermined KKM is 17 students with a percentage of 89.57%.